Taxpayer compliance improvement strategy motor vehicles - Margareta Diana Pangastuti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
North Central Timor Regency is one of the regencies in East Nusa Tenggara Province which is located directly adjacent to the Democratic State of Timor Leste. One of the most crucial development problems in this region is the problem of poverty. The most reliable local revenue sector is the tax sector, including motor vehicle tax. However, the facts on the ground show that the number of people who do not pay motor vehicle tax is still very high. This study aims to determine the partial and simultaneous effect of taxpayer awareness variables, service quality, taxpayer knowledge, taxpayer income and sanctions on taxpayer compliance and how to determine the right strategy in order to improve motor vehicle taxpayer compliance in Central Timor district. North. The analytical tools used are multiple linear regression and Process Hierarchical Analysis (AHP). The results showed that all variables had a significant effect on taxpayer compliance. Furthermore, the results of the Hierarchy Process Analysis study found that the most important element in determining policy priorities in an effort to improve motor vehicle taxpayer compliance is the application of E-Government.